Walking on uneven ground: How do patients with unilateral cerebral palsy adapt?. (April 2020) - Romkes, Jacqueline; Freslier, Marie; Rutz, Erich; Bracht-Schweizer, Katrin
Abstract: Background: Children with cerebral palsy experience movement disorders that influence gait stability. It is likely that gait stability further decreases when walking on uneven compared to even ground. Therefore, the aim of this study was to investigate gait on uneven ground in children with unilateral cerebral palsy. Methods: Twenty children with unilateral cerebral palsy and twenty typically developing children performed a three-dimensional gait analysis when walking on even and uneven ground. Spatio-temporal parameters, full-body joint kinematics and centre of mass displacements were compared. Findings: On uneven versus even ground, both groups showed decreased cadence, increased stance phase and double support time, increased toe clearance height, and increased knee and hip flexion during swing phase. Whereas only the typically developing children walked slower and had increased dorsiflexion and external foot progression during stance phase, only the patients showed increased stride width, increased elbow flexion (affected and non-affected side), and kept the centre of mass more medial when standing on the affected leg. Interpretation: Patients and healthy children use similar adaptation mechanisms when walking on uneven ground. Both groups increased the toe clearance height by increasing knee and hip flexion during swing. However, whereas patients enlarge their base of support by increasing stride width, healthy children do so by increasing their external foot progression angle. Furthermore, patients seem to feel more insecure and hold their arms in a position to prepare for falls on uneven ground. They also do not compensate with their non-affected side for their affected side on uneven ground. Highlights: Adaptive mechanisms when walking on uneven ground in patients with unilateral cerebral palsy Patients and healthy children show similar adaptive mechanisms on uneven ground. Different strategies to maintain dynamic stability on uneven ground were discovered. Patients do not compensate with their non-affected side for their affected side on uneven ground.